Elucidation of the Average Molecular Structure of Argentinian Asphaltenes - Bava, Yanina Belén (2019)
Petroleum asphaltenes were separated from three different Argentinian crude oils. The asphaltene fractions were extracted by precipitation employing n-pentane and n-heptane solvents, and the coprecipitated resins were removed via Soxhlet extraction. The asphaltenes were characterized by elemental analysis, thermogravimetric analysis, laser desorption ionization mass spectrometry, Fourier-transform infrared spectroscopy, proton nuclear magnetic resonance, powder X-ray diffraction, and Raman spectroscopy. It was found that the asphaltene fractions present both a higher content of heteroatoms and a major degree of aromaticity, when n-heptane is employed. Average structural parameters were obtained by a comprehensive analysis of the experimental data, including those describing the central polycyclic aromatic hydrocarbon (PAH) cores and lateral chains. Thus, a hypothetical average molecular structure is proposed for the Argentinian asphaltenes. The average model molecules have a nucleus of PAHs arranged as pericondensed systems of 4-6 fused aromatic rings, with naphthenic groups and/or alkyl chains of 5-10 carbon long attached.